2021
DOI: 10.3390/foods10040739
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin and Naringin Improve Broiler Meat Fatty Acid Profile and Modulate the Expression of Genes Involved in Fatty Acid β-oxidation and Antioxidant Defense in a Dose Dependent Manner

Abstract: The beneficial properties of the flavanones hesperidin and naringin as feed additives in poultry have lately been under investigation. In broilers, both flavanones have been shown to exhibit antioxidant properties while their individual effects on fatty acid (FA) composition and the underlying molecular mechanisms of their activity have not been explored. Here, we studied their effects on broiler meats’ FA profiles and on the expression of genes related to lipid metabolism, antioxidant defense and anti-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…Fotakis et al ( Fotakis et al, 2017 ) demonstrated that when supplemented in the broiler diet (0.70–1.5 g/kg), hesperidin reduced serum lipid content and significantly increased plasma alanine. Hager-Theodorides et al ( Hager-Theodorides et al, 2021 ) also found that the addition of hesperidin and naringenin to the broiler diet increased omega n-6 FA and PUFA/SFA ratios in breast muscle and fat pads. An explanation for these observed effects on fatty acid composition is that hesperidin and naringenin can enhance the expression of genes encoding factors related to fatty acid β-oxidation as well as fatty acid synthesis.…”
Section: Flavonoidsmentioning
confidence: 93%
See 2 more Smart Citations
“…Fotakis et al ( Fotakis et al, 2017 ) demonstrated that when supplemented in the broiler diet (0.70–1.5 g/kg), hesperidin reduced serum lipid content and significantly increased plasma alanine. Hager-Theodorides et al ( Hager-Theodorides et al, 2021 ) also found that the addition of hesperidin and naringenin to the broiler diet increased omega n-6 FA and PUFA/SFA ratios in breast muscle and fat pads. An explanation for these observed effects on fatty acid composition is that hesperidin and naringenin can enhance the expression of genes encoding factors related to fatty acid β-oxidation as well as fatty acid synthesis.…”
Section: Flavonoidsmentioning
confidence: 93%
“…Addition of hesperidin to the poultry diet can improve antioxidant capacity, health and egg production, reduce serum and yolk cholesterol content in laying hens ( S.Ting et al, 2011 ), and improve the fatty acid profile by reducing SFA and increasing polyunsaturated fatty acids (PUFA) content in broilers ( Hager-Theodorides et al, 2021 ), and bolster the immune response against lipopolysaccharide (LPS) ( Kawaguchi et al, 2004 ). Fotakis et al ( Fotakis et al, 2017 ) demonstrated that when supplemented in the broiler diet (0.70–1.5 g/kg), hesperidin reduced serum lipid content and significantly increased plasma alanine.…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase was advanced to d 2 in the breast meat of W1, but no increase in TBARS was observed in W2 and W3. Increasing VE in the diet improves the content of monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) in breast and thigh meat [30,33]. These unsaturated fatty acids are sensitive to lipid oxidation and might be one reason for the higher TBARS on d 6 of the control and d 2 of W1, where VE accumulation was not enough to prevent lipid peroxidation.…”
Section: Lipid Oxidative Stabilitymentioning
confidence: 99%
“…The number of studies on naringin's application in livestock and poultry production is relatively minor and single. Most studies have focused on naringin's effects on fat metabolism, meat quality, and livestock and poultry body immunity ( Simitzis et al., 2019 ; Hager-Theodorides et al., 2021 ). Therefore, the purpose of this study was to explore the protective effect of naringin on the follicular development of laying hens during late laying period.…”
Section: Introductionmentioning
confidence: 99%